2020
DOI: 10.1108/reps-12-2019-0162
|View full text |Cite
|
Sign up to set email alerts
|

Oil price fluctuations and economic growth: the case of MENA countries

Abstract: Purpose This paper aims to explore the extreme effect of crude oil price fluctuations and its volatility on the economic growth of Middle East and North Africa (MENA) countries. It also investigates the asymmetric and dynamic relationship between oil price and economic growth. Further, a separate analysis for each MENA oil-export and oil-import countries is conducted. Furthermore, it studies to what extent the quality of institutions will change the effect of oil price fluctuations on economic growth. Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 67 publications
(61 reference statements)
5
24
0
Order By: Relevance
“…They found that positive changes and negative changes in oil prices affected the stock market returns in Jordan and Morocco, respectively. Consistently, Abdelsalam (2020) found the same results for 17 MENA countries including Egypt, Morocco, and Jordan. However, Al-Fayoumi (2009) examined the relationship between oil price and stock market returns of Turkey, Tunisia, and Jordan as oil-importing countries over the period (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008).…”
Section: Introductionsupporting
confidence: 70%
“…They found that positive changes and negative changes in oil prices affected the stock market returns in Jordan and Morocco, respectively. Consistently, Abdelsalam (2020) found the same results for 17 MENA countries including Egypt, Morocco, and Jordan. However, Al-Fayoumi (2009) examined the relationship between oil price and stock market returns of Turkey, Tunisia, and Jordan as oil-importing countries over the period (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008).…”
Section: Introductionsupporting
confidence: 70%
“…The asymmetric influence of oil price volatility on economic advancement particularly on sectorial level was the focus of some recent studies such as the Mexican Rodríguez-Benavides et al ( 2022); his results showed that the oil costs effect on sectorial level effected only the second level sectors not the primary sectors of economic, therefore, policy makers must mitigate the effect of uncertainty in oil market in order to avoid any economic instabilities. The same conclusion also was approved in MENA countries by (Abdelsalam, 2020;Ahmed, 2016) after examining the speculated effects of oil prices on MENA countries, the results of his study supported the proposed expectation for the negative impact of oil prices on economic growth. In middle east region such as Jordan (Al Nsour and Malkawi, 2019;Tahtamouni et al, 2017;Bash, 2015) and Lebanon (Ghalayini, 2011) approved the negative impact of oil prices on GDP, they found that as long as the oil importing costs decrease the GDP arise.…”
Section: Literature Reviewsupporting
confidence: 64%
“…used structural VAR model to assess the influence of coronavirus shocks on the energy futures markets, specifically on the S&P GS Indexes for crude oil and natural gas. The authors found that energy commodities respond to COVID-19 shocks in different ways over time, depending on fundamentals, behavioral, and psychological aspects ( Abdelsalam, 2020 ). investigate the extreme impact of oil price volatility on the economic performance in the MENA countries.…”
Section: Introductionmentioning
confidence: 99%